2004
DOI: 10.1161/01.cir.0000147774.90396.ed
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Prevents Vascular Hyporeactivity During Inflammation

Abstract: Background-There is growing evidence that statins exert anti-inflammatory and antioxidative vascular actions that are independent of lipid lowering. We tested whether hyporeactivity to the endothelium-dependent vasodilator acetylcholine (ACh) and the vasoconstrictor norepinephrine (NE) during acute experimental inflammation could be prevented by simvastatin. Methods and Results-In a randomized, placebo-controlled, parallel group study, forearm blood flow (FBF) responses to NE, ACh, and the endothelium-independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 52 publications
3
75
1
2
Order By: Relevance
“…Another study showed that 1-h exposure to TNF-α, IL-1β, or endotoxin impairs endothelial function in hand veins of healthy subjects (Bhagat et al 1996). Endothelial NIH-PA Author Manuscript NIH-PA Author Manuscript NIH-PA Author Manuscript dysfunction is also produced by intra-arterial endotoxin infusion, and this impairment can be prevented by pretreatment with a statin (Pleiner et al 2004). …”
Section: Human Studies Of Systemic Inflammation and Endothelial Dysfumentioning
confidence: 99%
“…Another study showed that 1-h exposure to TNF-α, IL-1β, or endotoxin impairs endothelial function in hand veins of healthy subjects (Bhagat et al 1996). Endothelial NIH-PA Author Manuscript NIH-PA Author Manuscript NIH-PA Author Manuscript dysfunction is also produced by intra-arterial endotoxin infusion, and this impairment can be prevented by pretreatment with a statin (Pleiner et al 2004). …”
Section: Human Studies Of Systemic Inflammation and Endothelial Dysfumentioning
confidence: 99%
“…Human studies have demonstrated positive association between systemic inflammation induced by endotoxin infusion and marked endothelial dysfunction as well as impaired responses to vasoactive compounds (Pleiner et al, 2004). An analysis of the Framingham Heart Study Offspring cohort found that serum C-reactive protein, IL-6, and soluble intercellular adhesion molecule-1 levels inversely correlated with brachial artery flow-mediated dilation and reactive hyperemia in the forearm, although this relationship was weakened after adjusting for traditional risk factors (Vita et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Besides their cholesterollowering effect, statins have anti-inflammatory and immunomodulatory benefits. They can inhibit lipopolysaccharide (LPS)-mediated activation of human peripheral mononuclear cells and endothelial cells (18) and reduce the level of the proinflammatory cytokines tumor necrosis factor ␣ (TNF-␣) and interleukin (IL)-6 (23), thereby suppressing vascular inflammation and stabilizing vulnerable plaques (17). However, little is known about the mechanisms responsible for these anti-inflammatory effects.…”
mentioning
confidence: 99%